If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5 + -1x) + -3(1 + -2x) = 42 (5 * 3 + -1x * 3) + -3(1 + -2x) = 42 (15 + -3x) + -3(1 + -2x) = 42 15 + -3x + (1 * -3 + -2x * -3) = 42 15 + -3x + (-3 + 6x) = 42 Reorder the terms: 15 + -3 + -3x + 6x = 42 Combine like terms: 15 + -3 = 12 12 + -3x + 6x = 42 Combine like terms: -3x + 6x = 3x 12 + 3x = 42 Solving 12 + 3x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3x = 42 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = 42 + -12 3x = 42 + -12 Combine like terms: 42 + -12 = 30 3x = 30 Divide each side by '3'. x = 10 Simplifying x = 10
| 3t-8t-3=0 | | 6x+9=2x-4 | | 2a+4+4a+b+5b= | | 5x+7=25 | | 27+5.8-6=37 | | x^2-36-9x=0 | | -2+1=-5 | | 27+5.8-6=36 | | x+(x-30)+4(x-30)=120 | | 2(2x-1)+6=4(1+x) | | 6(x+7)=x+25 | | x+3x+(3x+30)=120 | | 5m-4=-7 | | 2p(p-6p+1)= | | x+3x+(3x-30)=120 | | d-7=-21 | | 625+14641=x^2 | | x+30x+(30x-3)=120 | | a-4.8=5.9 | | 6m(4+m)= | | 11+3x-7=6x+5-3x | | 144+x^2-169=0 | | p^2+2p+8=0 | | 3(b+6)=5(b+-1) | | 77k=77 | | (z+5)2z= | | 8x=7x-25 | | 5t-3+4t=6+2t-9 | | x^2+16-25=0 | | 5(12-3w)=15w+60 | | (2x+5)+(7x-8)=360 | | 3w(w+2)= |